A Phase I Study to Assess the Safety and Cancer-Homing Ability of Allogeneic Bone Marrow-Derived Mesenchymal Stem Cells in Men with Localized Prostate Cancer. (8th February 2019) - Schweizer, Michael T.; Wang, Hao; Bivalacqua, Trinity J.; Partin, Alan W.; Lim, Su Jin; Chapman, Carolyn; Abdallah, Rehab; Levy, Oren; Bhowmick, Neil A.; Karp, Jeffrey M.; De Marzo, Angelo; Isaacs, John T.; et al.
Abstract: Animal models show that systemically administered bone marrow-derived mesenchymal stem cells (MSCs) home to sites of primary and metastatic prostate cancer (PC)—making them candidates to selectively deliver cytotoxic agents. To further assess this potential as a cell-based therapeutic vehicle, a phase I study testing homing of systemically infused allogeneic MSCs preprostatectomy was conducted. The primary objective was to assess safety and feasibility and to determine if MSCs accumulate within primary PC tissue. MSCs were quantified using beads, emulsion, amplification, magnetics digital polymerase chain reaction (limit of detection: ≥0.01% MSCs) to measure allogeneic MSC DNA relative to recipient DNA. MSCs were harvested from healthy donors and expanded ex vivo using standard protocols by the Johns Hopkins Cell Therapy Laboratory. PC patients planning to undergo prostatectomy were eligible for MSC infusion. Enrolled subjects received a single intravenous infusion 4–6 days prior to prostatectomy. The first three subjects received 1 x 10 6 cells per kilogram (maximum 1 x 10 8 cells), and subsequent four patients received 2 x 10 6 cells per kilogram (maximum 2 x 10 8 cells). No dose-limiting toxicities were observed and all patients underwent prostatectomy without delay. Pathologic assessment of prostate cores revealed ≥70% tumor involvement in cores from four subjects, with benign tissue in the others. MSCs were undetectable in all subjects, and the study was stopped early for futility. MSC infusions appear safe in PC patients. Although intended for eventual use in metastatic PC patients, in this study, MSCs did not home primary tumors in sufficient levels to warrant further development as a cell-based therapeutic delivery strategy using standard ex vivo expansion protocols. Stem Cells Translational Medicine 2019;8:441–449 : Abstract : Mesenchymal stem cells (MSCs) have an innate tropism for sites of cancer. To assess their potential as a cell-based therapeutic vehicle, a Phase I study testing systemically infused MSCs pre-prostatectomy was conducted in men with localized prostate cancer. The primary objective was to assess safety and feasibility of allogeneic MSC infusion, and to determine if MSCs accumulate within primary PC tissue. MSCs were quantified using BEAMing digital PCR (limit of detection: ≥0.01% MSCs) to measure allogeneic MSC DNA relative to recipient DNA.